1999
DOI: 10.1055/s-2008-1072248
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Translocation is Favored by the Preservation of the Ileocecal Valve in Experimental Short Bowel with Total Parenteral Nutrition

Abstract: Sepsis in short-bowel syndrome (SBS) is in part due to bacterial translocation (BT). Parenteral nutrition (PN) is often necessary in SBS and promotes BT. The aim of this study was to asses the effect of the presence or absence of ileocecal valve (ICV) on BT in parenterally-fed rats with massive intestinal resection. Sixty-five adult Wistar rats underwent central venous cannulations and were randomly assigned to one of five groups receiving for ten days five treatment regimes: Sham (n = 17) standard rat chow + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Increased bacterial translocation to the lymph nodes and portal blood has previously been observed in resected rodents compared with nonresected, although those rodents were fed enterally. A prior study in adult Wistar rats also found increased bacterial translocation in gut‐resected animals, whether enterally or PN fed . Interestingly, that study also found that PN‐fed rats without the ICV had reduced bacterial translocation compared with those with the ICV.…”
Section: Discussionmentioning
confidence: 69%
“…Increased bacterial translocation to the lymph nodes and portal blood has previously been observed in resected rodents compared with nonresected, although those rodents were fed enterally. A prior study in adult Wistar rats also found increased bacterial translocation in gut‐resected animals, whether enterally or PN fed . Interestingly, that study also found that PN‐fed rats without the ICV had reduced bacterial translocation compared with those with the ICV.…”
Section: Discussionmentioning
confidence: 69%
“…With the intact ICV, fewer patients required PN, the time of weaning from PN was shorter, and the number of patients weaned was larger [10]. However, recent experimental studies demonstrated that additional resection of ICV to SBR significantly decreased the incidence of bacterial translocation with the explanation that prolongation of the intestinal transit time by ICV might play a role in the 'bacterial translocation' [13,14]. Our study presented crucial effects of ICV on short bowel syndrome.…”
Section: Discussionmentioning
confidence: 70%
“…In several animal models it has been demonstrated that bacterial translocation to the mesenteric lymph nodes, liver and spleen is increased after intestinal resection [18][19][20] . Although in this study we have not studied bacterial translocation, it is speculated that the mechanism for this to occur is not yet known, but hardly is secondary to simple changes in intestinal permeability after ileal resection 21 .…”
Section: Discussionmentioning
confidence: 99%